Lead Discovery for Human Kynurenine 3-Monooxygenase by High-Throughput RapidFire Mass Spectrometry. (April 2014) - Lowe, Denise M.; Gee, Michelle; Haslam, Carl; Leavens, Bill; Christodoulou, Erica; Hissey, Paul; Hardwicke, Philip; Argyrou, Argyrides; Webster, Scott P.; Mole, Damian J.; Wilson, Kris; Binnie, Margaret; et al.
Kynurenine 3-monooxygenase (KMO) is a therapeutically important target on the eukaryotic tryptophan catabolic pathway, where it converts L-kynurenine (Kyn) to 3-hydroxykynurenine (3-HK). We have cloned and expressed the human form of this membrane protein as a full-length GST-fusion in a recombinant baculovirus expression system. An enriched membrane preparation was used for a directed screen of approximately 78, 000 compounds using a RapidFire mass spectrometry (RF-MS) assay. The RapidFire platform provides an automated solid-phase extraction system that gives a throughput of approximately 7 s per well to the mass spectrometer, where direct measurement of both the substrate and product allowed substrate conversion to be determined. The RF-MS methodology is insensitive to assay interference, other than where compounds have the same nominal mass as Kyn or 3-HK and produce the same mass transition on fragmentation. These instances could be identified by comparison with the product-only data. The screen ran with excellent performance (average Z′ value 0.8) and provided several tractable hit series for further investigation.